Opportunities and challenges of incretin-based hypoglycemic agents treating type 2 diabetes mellitus from the perspective of physiological disposition - Yaochen Xie; Qian Zhou; Qiaojun He; Xiaoyi Wang; Jincheng Wang (Elsevier, 2023)
The treatment of patients with diabetes mellitus, which is characterized by defective insulin secretion and/or the inability of tissues to respond to insulin, has been studied for decades. Many studies have focused on the use of incretin-based hypoglycemic agents in treating type 2 diabetes mellitus (T2DM). These drugs are classified as GLP-1 receptor agonists, which mimic the function of GLP-1, and DPP-4 inhibitors, which avoid GLP-1 degradation. Many incretin-based hypoglycemic agents have been approved and are widely used, and their physiological disposition and structural characteristics are crucial in the discovery of more effective drugs and provide guidance for clinical treatment of T2DM. Here, we summarize the functional mechanisms and other information of the drugs that are currently approved or under research for T2DM treatment. In addition, their physiological disposition, including metabolism, excretion, and potential drug-drug interactions, is thoroughly reviewed. We also discuss similarities and differences in metabolism and excretion between GLP-1 receptor agonists and DPP-4 inhibitors. This review may facilitate clinical decision making based on patients' physical conditions and the avoidance of drug-drug interactions. Moreover, the identification and development of novel drugs with appropriate physiological dispositions might be inspired.